2022
DOI: 10.1177/18479804221085103
|View full text |Cite
|
Sign up to set email alerts
|

Immunosensing the rheumatoid arthritis biomarker through bifunctional aldehyde-amine linkers on an iron oxide nanoparticle seeded voltammetry sensor

Abstract: An immunosensor was developed on an interdigitated electrode (IDE) by voltammetry sensing for the early identification of the autoimmune disease ‘rheumatoid arthritis (RA)’ by detecting the biomarker anti-cyclic citrullinated peptide antibody (anti-CCP). Higher immobilization of cyclic citrullinated peptide (CCP) as a probe was achieved by using green synthesized iron oxide nanoparticles (IONPs). Field-emission scanning electron microscopy and field-emission transmission electron microscopy observations reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The use of GA and the green-chemistry synthesis of the IONPs make this platform simple and cost-effective. The obtained results showed a linear range from 8 to 250 pg/mL, with a limit of detection of about 15 pg/mL, thereby indicating its application to quantify anti-CCP levels in the biological fluid in order to diagnose RA [ 197 ].…”
Section: Autoimmune Disease Biosensingmentioning
confidence: 99%
“…The use of GA and the green-chemistry synthesis of the IONPs make this platform simple and cost-effective. The obtained results showed a linear range from 8 to 250 pg/mL, with a limit of detection of about 15 pg/mL, thereby indicating its application to quantify anti-CCP levels in the biological fluid in order to diagnose RA [ 197 ].…”
Section: Autoimmune Disease Biosensingmentioning
confidence: 99%
“…ACPAs, a well-known biomarker of RA, as already mentioned, were detected by an electrochemical immunosensor using interdigitated electrodes, the surfaces of which were suitably modified with a cyclic citrullinated peptide loaded on iron oxide nanoparticles. The nanoparticles were synthesized with a "green-chemistry" approach based on a plant extract and chemically immobilized on the sensing surface by means of 3-aminopropyltriethoxysilane and glutaraldehyde [18]. Another electrochemical immunosensor for the The sensors can be divided into two broad categories, i.e., those detecting autoantibodies (I) and those detecting other protein biomarkers (II).…”
Section: Ad Immunosensors Detecting Autoantibodiesmentioning
confidence: 99%
“…For instance, green synthesis of magnetic iron oxide nanocomposite deposited on cellulose nanocrystals with copper for the development of a venlafaxine electrochemical sensor, 235 α-Fe 2 O 3 nanoparticles synthesized by using a simple hydrothermal process for electron mediator in efficient chemical sensor, 236 and iron oxides nanoparticles fabricated via plant (Durian) extract media for immunosensor. 237 Iron oxides in the thin film form may be much more suitable for electronic device applications. 17,238 In the thin film form, they can be easily incorporated into active or passive electronic devices.…”
Section: Recent Applications Of Nanometer-sizedmentioning
confidence: 99%
“…Excellent electronics, optic, and magnetic properties of iron oxides make iron oxides a prototype of the ideal functional material for many applications, including for electronic devices. , Nanometer-sized iron oxide also has been utilized in sensor device applications such as gas and humidity sensors, strain sensors, magnetic sensors, and biosensors. For instance, α-Fe 2 O 3 for spin-valve in memory device application, because of its excellent antiferromagnetic properties, , ε-Fe 2 O 3 for spintronic devices, because of its multiferroic properties, and β-Fe 2 O 3 for sensor and battery anode applications, because of its excellent electrochemical behavior. , Many previous reports have shown that the green synthesis of nanometer-sized iron oxides could be used in electronic devices. For instance, green synthesis of magnetic iron oxide nanocomposite deposited on cellulose nanocrystals with copper for the development of a venlafaxine electrochemical sensor, α-Fe 2 O 3 nanoparticles synthesized by using a simple hydrothermal process for electron mediator in efficient chemical sensor, and iron oxides nanoparticles fabricated via plant (Durian) extract media for immunosensor . Iron oxides in the thin film form may be much more suitable for electronic device applications. , In the thin film form, they can be easily incorporated into active or passive electronic devices. Various attempts have been devoted to obtaining green synthesis of iron oxide thin films, for example, green synthesis of iron oxide thin films grown from recycled iron foils .…”
Section: Recent Applications Of Nanometer-sized Iron Oxides Synthesiz...mentioning
confidence: 99%